TRADITIONS AND INNOVATIVE APPROACHES IN NATIONAL SPORTS GAMES AND ART - qizi, Salimova Shahzoda Zayniddin (Research Focus International Scientific Journal, 2026)
This article examines the topic “Milliy Sport O‘Yinlari Hamda San’Atda An’Analar Va Innovatsion Yondashuvlar” from a scientific and methodological perspective. The theoretical foundations, practical significance and relevant aspects of the study are analysed.